Explicit reasoning, confirmation bias and illusory transactive memory a simulation study of group medical decision making - Tschan, Franziska; Semmer, Norbert K. ([Place of publication not identified] Sage Publichations, 2009)
Teamwork is important in medicine, and this includes team-based diagnoses. The influence of communication on diagnostic accuracy in an ambiguous situation was investigated in an emergency medical simulation. The situation was ambiguous in that some of the patient's symptoms suggested a wrong diagnosis. Of 20 groups of physicians, 6 diagnosed the patient, 8 diagnosed with help, and 6 missed the diagnosis. Based on models of decision making, we hypothesized that accurate diagnosis is more likely if groups (a) consider more information, (b) display more explicit reasoning, and (c) talk to the room. The latter two hypotheses were supported. Additional analyses revealed that physicians often failed to report pivotal information after reading in the patient chart. This behavior suggested to the group that the chart contained no critical information. Corresponding to a transactive memory process, this process results in what we call illusory transactive memory. The plausible but incorrect diagnosis implied that the two lungs should sound differently. Despite objectively identical sounds, some physicians did hear a difference, indicating confirmation bias. Training physicians in explicit reasoning could enhance diagnostic accuracy.
Includes bibliographical references.
Keywords: Group process analysis; Medical emergency